Teachers’ Strategies in Teaching English Conversation Skills - Istiqlaliah Nurul Hidayati; Salwana Wafa; Lungguh Halira Vonti (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2026)
English conversation activities are widely recognized as effective in enhancing students’ speaking proficiency by providing meaningful opportunities for communicative practice in the classroom. This study was conducted in an Indonesian junior high school that offers a supplementary subject called Daily English Conversation, which aims to develop students’ spoken English through various instructional strategies. The purpose of this study was to investigate the teacher’s strategies in teaching English conversation. This research employed a qualitative case study design involving one teacher who taught the Daily English Conversation class as the main participant. Data were collected through classroom observations, documentation, and semi-structured interviews to gain an in-depth understanding of the teaching strategies used. The findings showed that the teacher implemented several strategies, including role-play, pair work, group discussions, and interview activities. These strategies were applied to encourage active student participation, promote authentic communication, and build students’ confidence in expressing ideas in English. The study concludes that the use of varied conversational strategies can effectively create a more interactive and communicative learning environment. Future research is recommended to examine the implementation of similar strategies at different educational levels, investigate their long-term impact on students’ communicative competence, and explore innovative approaches to teaching English speaking skills.